A learning model promoting higher-order thinking skills and active citizenship with global mindedness - Dhanita Doungwilai; Issara Kanjug (International Journal of Evaluation and Research in Education (IJERE), 2023)
The objectives of this research were to study the current situation of and the needs for teacher competency development in learning management, and to develop a learning management model. The sample was 95 teachers selected by simple random sampling. Research instruments were a questionnaire and a learning management model created through the process of drafting, evaluation and verification, and improvement. Statistics used for data analysis were mean, percentage, and standard deviation. The findings indicated teachers’ opinions towards the current situation of learning management that promotes critical thinking skills and active citizenship with global mindedness at a high level. The need for developing learning management competency were also at a highest level. Components of the learning management model include: i) Basic principles and concepts; ii) Learning objectives; iii) Learning process and learning assessment; and iv) Learning outcomes. The teacher development process includes: professional learning community (PLC), guidelines for learning management, design of learning management, measurement and evaluation, teaching practicum, supervision, reflection, and lesson learned. The model showed the suitability at a highest level.